The essential meaning of Maantat tradition in Ladang Panjang Village, Sarolangun Regency, Jambi, Indonesia - Rahmi, Nur Amilia Kartika; Wirdanengsih, Wirdanengsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Maantat is one of the ancestral traditions of the Malay tribe, and it is still preserved in the Jambi region, Sumatra. The Malay people in Jambi practice this tradition on important days, such as Islamic religious holidays and weddings. This study aimed to determine the meaning or important values ​​in implementing the Maantat tradition that make this tradition sustainable until now. The method used is descriptive qualitative with an ethnographic approach. Data collection techniques use observation and interview techniques. The study was conducted in Ladang Panjang Village, Sarolangun, Jambi. This study found that Maantat is a tradition of delivering food in containers (rantang) to relatives during critical events. The essential values ​​contained in it are fostering a sense of togetherness and solidarity, the manifestation of gratitude, and respect for elders and customs, all of which are manifestations of the noble values ​​of Indonesian society that prioritize relationships between individuals, spirituality, and respect for tradition.